Salivary gland calculus - A painless and self-regressing swelling - Arpan Manna (Wolters Kluwer Medknow Publications, 2022)
Salivary gland disorder occurs commonly because of salivary calculi, which may occur at any age and involves any of the salivary glands. Most of the cases of sialolithiasis occur in the submandibular salivary gland as its duct is most prone to and common for acute and chronic infections. The symptoms include decreased or obstructed salivary flow. This case report presents a case of a patient with sialolithiasis of the submandibular gland and its treatment. It also includes etiology, signs and symptoms, diagnosis, and various treatment modalities.